E-homework is widening the gap for disadvantaged students - Dobozy, Eva (The Conversation, 2014)
More and more teachers are turning to technology when assigning homework. But while e-homework can make out-of-class learning more fun and interactive, research suggests that it might further disadvantage students from low socio-economic families.